1998
DOI: 10.1007/s002770050395
|View full text |Cite
|
Sign up to set email alerts
|

A 66-year-old woman with nephrotic syndrome and an IgM monoclonal gammopathy

Abstract: Presentation of caseIn September 1996, a 66-year-old woman visited our clinic because of edema of the legs of 4 month's duration. Her family doctor reported a high erythrocyte sedimentation rate of 136 mm in the first hour, marked proteinuria, and the presence of a monoclonal band on serum electrophoresis. In March of the same year she had undergone a total abdominal hysterectomy for a myoma with bilateral salpingo-oophorectomy. Her medical history was otherwise unremarkable.In addition to her edema, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In this case, PE and cytotoxic drugs allowed the discontinuation of hemodialysis (42). Nephrotic syndrome with significant albuminuria also may result from amyloidosis (43,44). Gertz et al reported on 50 cases of IgM monoclonal gammopathy and biopsy proven amyloidosis in which 32% had renal involvement (43).…”
Section: Renal Involvement In Hyperviscosity Syndrome and Waldenstrommentioning
confidence: 88%
“…In this case, PE and cytotoxic drugs allowed the discontinuation of hemodialysis (42). Nephrotic syndrome with significant albuminuria also may result from amyloidosis (43,44). Gertz et al reported on 50 cases of IgM monoclonal gammopathy and biopsy proven amyloidosis in which 32% had renal involvement (43).…”
Section: Renal Involvement In Hyperviscosity Syndrome and Waldenstrommentioning
confidence: 88%
“…In this case, PE and cytotoxic drugs allowed the discontinuation of hemodialysis (42). Nephrotic syndrome with significant albuminuria also may result from amyloidosis (43,44). Gertz et al reported on 50 cases of IgM monoclonal gammopathy and biopsy proven amyloidosis in which 32% had renal involvement (43).…”
Section: Renal Involvementmentioning
confidence: 88%
“…Light chain deposition disease is another frequent complication of monoclonal gammopathies (22), although infrequently associated with IgM monoclonal gammopathies. Other causes of nephrotic syndrome (23) occasionally reported with IgM monoclonal gammopathies are minimal change nephrotic syndrome, anti‐GMB antibody‐induced glomerulonephritis, immune complex‐mediated glomerulonephritis, and membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%